Upper body resistance exercise reduces time to recover following a high-volume bench press protocol in resistance trained men - Bartolomei, S.; Tott, V.; Nigro, F.; Ciacci, S.; Semprini, G.; Cortesi, M.; Di Michele, R. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The aim of this study was to investigate the effects of different recovery strategies on the recovery response following a high-volume bench press protocol. Methods: Twenty-five resistance trained men (Mean ± SD: age = 25.8 ± 3.6 y body mass = 87.1 ± 12.1 kg: height = 177.4 ± 4.9 cm) performed a high-volume bench press session (8 sets of 10 reps at 70% of 1RM). Subsequently, they were randomly assigned to an active recovery (AR) group (n = 11) or to a passive recovery (PR) group (n = 14). AR consisted of light bench press sessions performed 6 hr and 30 hr after the high-volume exercise protocol. Muscle performance [bench throw power (BTP) and isometric bench press (IBP)] and morphology [muscle thickness of pectoralis major (PECMT) and of triceps brachii (TRMT)] were measured prior to exercise (BL). and at15-min (15P). 24-hr(24P) and 48-hr (48P) post-exercise. Results: Post-exercise recovery of both maximal strength and power were accelerated in AR compared to PR. Both BTP and IBP were significantly (p<0.001) reduced at 15P and 24P in PR while changes were significant (p<0.001) at 15P only in AR. PECMT was still significantly (p=0.015) altered from BL at 48P in PR while changes were significant (p<0.001) at 15P only in AR (see Figure 1). No significant interactions (p>0.05) between PR and AR were detected for TRMT and muscle soreness. Conclusion: The present results indicate that AR enhances the recovery rate of both performance and muscle morphology following a high-volume exercise session for upper body.